Problematic Division of Inheritance in Personal Assessment and the Perspective of Islamic Law and Positive Laws - Fikri Al Muhaddits Dalimunthe; Syafruddin Syam; Nurcahaya Nurcahaya (Electronic Journal of Education, Social Economics and Technology, 2025)
Inheritance distribution is an essential part of resolving the assets left by a deceased individual. However, problems arise when the inheritance includes not only personal assets but also assets registered under the name of a foundation. In Islamic law, inheritance can only be distributed from assets personally owned by the deceased. In contrast, under Indonesian positive law specifically Law No. 16 of 2001 in conjunction with Law No. 28 of 2004 on Foundations foundation assets are not considered the private property of the founder, but are part of a legal entity. This study aims to analyze the issues in inheritance distribution involving personal and foundation assets from the perspective of Islamic law and positive law. This research employs a qualitative method with a normative-juridical approach. The results indicate that the misuse of foundation assets as part of an inheritance often leads to conflicts among heirs. Therefore, a thorough understanding and harmonization between the two legal systems are necessary to ensure fair and lawful inheritance distribution.